Association of insecticide use and alteration on Aedes aegypti susceptibility status - Maria de Lourdes da Graça Macoris; Maria Teresa Macoris Andrighetti; Vanessa Camargo Garbeloto Otrera; Lídia Raquel de Carvalho; Antonio Luiz Caldas Júnior; William G Brogdon (Memorias do Instituto Oswaldo Cruz, 2007)
Dengue and dengue hemorrhagic fever, vector-borne diseases transmitted by the mosquito Aedes aegypti, are presently important public health problems in Brazil. As the strategy for disease control is based on vector control through the use of insecticides, the development of resistance is a threat to programs efficacy. The objective of this study was to compare the Aedes aegypti susceptibility in nine vector populations from the state of São Paulo and seven from Northeast region of Brazil, since there was a difference on group of insecticide used between the areas. Bioassays with larvae and adult were performed according to the World Health Organization methods.The results showed higher resistance levels to organophosphates group in populations from the Northeast region where this group was used for both larvae and adult control than in São Paulo where organophosphates were used for larvae and pyretroids for adult control. Resistance to pyretroids in adults was widespread in São Paulo after ten years of use of cypermethrin while in vector populations from the Northeast region it was punctual. The difference in resistance profile between the areas is in accordance to the group of insecticide used.